Trophic structure of coastal meta-ecosystems in the tropical Southwestern Atlantic. (5th December 2021) - Macedo, Morgana M.; Angelini, Ronaldo; da Silva, VictorE.L.; Fabré, Nidia N.
Abstract: Coastal and oceanic ecosystems have their own structural and functional dynamics, but they are typically connected by the transfer of nutrients and organisms. These organic matter and energy flows mean these environments function as a meta-ecosystem. In the tropics, the transfers between estuaries and the neritic ecosystems or nearshore can be driven by estuarization events, which are poorly understood. Here, we analyze the effects of seasonal estuarization on the trophic structure of estuarine and neritic ecosystems connected by biological and physical flows in space and time. Specifically, we evaluated trophic connectivity and the flow of fish species from the South Atlantic, based on the assumption of meta-ecosystem functionality. We used standard sampling gear and fishing effort to evaluate the estuarine and neritic ecosystems during the dry and the rainy seasons of the region. The diet and trophic niche of fish species were estimated for both environments. We also reconstructed the trophic connections between species and food items for each season to evaluate the changes in the food web of each environment. During the dry season, the estuarine and neritic ecosystems are both characterized by a simpler trophic structure in terms of biomass distribution among trophic levels, but in the rainy season, the migration of species associated with estuarine and oceanic ecosystems to the neritic ecosystem changed the trophic structure of this area. The movements of organisms between ecosystems increases the complexity of the trophic structure of neritic ecosystem, allowing the transfers of organic matter and energy, confirming this complex as a meta-ecosystem. Highlights: - Seasonal flows of species are important for the dynamics of connected ecosystems - Rainfall drives the distribution of tropical fishes in estuaries and the neritic zone - Species migrations between ecosystems create a trophic meta-ecosystem convergence